FOLIAR AND SOIL NUTRIENT STATUS OF SOME COMMON PLANTS OF ROCK AREAS AT AJMER, RAJASTHAN, INDIA - B.M., Sharma (วารสารวนศาสตร์ไทย, 2022)
Euphorbia caducifolia which is a dominant plant on the rocks grows well on loamy sand that has low cation exchange capacity, poor in sodium but rich in calcium and magnesium and chlorides. The plant possessed a high foliar and stem ash content. Certain nutrients, like calcium and phosporus were higher in leaves as compared to stem. Acacia senegal is another dominant tree on the rocks of Ajmer. The soils supporting the plant were loamy sand having a low cation exchange capacity. The leaves were rich in ash content and calcium.